Evaluation of Traditional Medicine Programs In Public Health Centre Mengwi, Bali - Ni Made Umi Kartika Dewi (Universitas Muhammadiyah Yogyakarta, 2018)
Public Health Centre in Mengwi is one of the Public Health Centre (PHC) that apply for traditional medicine program since 2012. However, the result of the program is still under the expected target. This study aims to evaluate the traditional medicine program at PHC in Mengwi. This study was a descriptive evaluation research with the qualitative method. Data collection used in-depth interviews with 11 informants. Data analysis was done by thematic analysis using the evaluation method of the program (input and process program). The result found in the lack of staff knowledge, this program had not been supported by special funding and facilities. The process of implementing the guidance and visits from PHC in Mengwi had not been done routinely. Traditional in healer has a low level of information about the requirements of making registered permit and registered letters of a traditional healer. The availability of inputs on the traditional medicine program at PHC in Mengwi is not optimal yet and the implementation process has not been run maximally. So, it is recommended for local government to use the result of program evaluation as the basis to provide further guidance for health workers and traditional healers.